2004
DOI: 10.1242/jcs.00905
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of the Hsp70/Hsp90 organizing protein mSTI1 is regulated by cell cycle kinases

Abstract: The co-chaperone murine stress-inducible protein 1 (mSTI1), an Hsp70/Hsp90 organizing protein (Hop) homologue, mediates the assembly of the Hsp70/Hsp90 chaperone heterocomplex. The mSTI1 protein can be phosphorylated in vitro by cell cycle kinases proximal to a putative nuclear localization signal (NLS), which substantiated a predicted casein kinase II (CKII)-cdc2 kinase-NLS (CcN) motif at position 180-239 and suggested that mSTI1 might move between the cytoplasm and the nucleus under certain cell cycle condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 44 publications
5
84
0
Order By: Relevance
“…There is evidence to suggest that localisation of Hop may be due to phosphorylation. Hop can be phosphorylated by cell cycle kinases, phosphorylation by cdc2 (cell division cycle 2) kinase promotes cytoplasmic retention, whereas phosphorylation by casein kinase II (CKII) promotes nuclear Hop, suggesting that Hop might move between the cytoplasm and the nucleus under certain cell cycle conditions [40,41]. The nuclear accumulation of Hop is primarily stress regulated and CKII phosphorylation has been shown not to disrupt Hop-Hsp90 binding [36].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that localisation of Hop may be due to phosphorylation. Hop can be phosphorylated by cell cycle kinases, phosphorylation by cdc2 (cell division cycle 2) kinase promotes cytoplasmic retention, whereas phosphorylation by casein kinase II (CKII) promotes nuclear Hop, suggesting that Hop might move between the cytoplasm and the nucleus under certain cell cycle conditions [40,41]. The nuclear accumulation of Hop is primarily stress regulated and CKII phosphorylation has been shown not to disrupt Hop-Hsp90 binding [36].…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced phosphoprotein-1 was shown to interact with Hsp70 and Hsp90 and facilitates transfer of substrates from Hsp70 to Hsp90 and is important for proper protein folding, maturation, and cell cycle progression (8,22,36,67). We propose that severe downregulation of stress-induced phosphoprotein-1 with high dose alone might have disturbed the key interaction between stress-induced phosphoprotein-1 and various HSPs, leading to cell death, compared with sustained expression of stress-induced phosphoprotein-1 and activation of survival pathways in autoprotected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Group III consisted of five mice to ensure a minimum of three surviving mice, because mice started dying between 108 and 120 h (36 -48 h after the high dose) in the lethality experiment (Table 1). Mice were terminated under diethyl ether anesthesia at 6,12,24,36,72,78,84,96,144,240, and 336 h after the low-dose administration in groups II and IV. Mice in group III (n ϭ 3/time point) were terminated after the administration of DW at 6,12,24,36,72,78,84,96, and 108 h. Plasma was collected from mice at each time point to assess renal function.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our in vitro kinase assay confirmed that Y354 was indeed the direct phosphorylation site of SYK. Besides, it is known that STIP1 promotes the association between 70 kDa heat shock cognate protein (HSC70) and heat shock protein 90 (HSP90) (52). HSC70 and HSP90 can be phosphorylated by SYK both in vitro and in vivo (28).…”
Section: Validating Novel Syk Substrates In Vitro and In Vivo-mentioning
confidence: 99%